Evaluation of the Risk of Spreading Endometrial Cell by Hysteroscopy: A Prospective Longitudinal Study - Rievani de Sousa Damião; Reginaldo Guedes Coelho Lopes; Emilly Serapião dos Santos; Umberto Gazzi Lippi; Eduardo Borges da Fonseca (Obstetrics and Gynecology International)
Objective. The aim was to assess the intraperitoneal spread of endometrial cells during hysteroscopy. Study Design. Seventy-six women were submitted to a hysteroscopy with CO2 under a low pressure. Group 1 had not previous diagnosis of endometrial cancer, and group 2 had previous diagnosis of endometrial cancer (stage I-92.3%). Two peritoneal washing samples were taken before (PW1) and immediately after (PW2) the procedure. The dissemination for the peritoneal cavity was defined by the presence of endometrial cells in the PW2; such cells should be absent in WP1. Results. Four patients were excluded for presenting endometrial cells in PW1. In the 72 patients left, there was no passage of cells for the peritoneal cavity. In group 1, 88% presented secretory endometrial phase with correlation of 80% between hysteroscopy and biopsy. Conclusion. Hysteroscopy performed under a low pressure of CO2 does not cause spreading of endometrial cells into the peritoneal cavity.